4n平方(m-2)-6(2-m)和4m平方n平方-(m平方+n平方)平方 分解因式
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 17:59:10
4n平方(m-2)-6(2-m)和4m平方n平方-(m平方+n平方)平方分解因式4n平方(m-2)-6(2-m)和4m平方n平方-(m平方+n平方)平方分解因式4n平方(m-2)-6(2-m)和4m平
4n平方(m-2)-6(2-m)和4m平方n平方-(m平方+n平方)平方 分解因式
4n平方(m-2)-6(2-m)和4m平方n平方-(m平方+n平方)平方 分解因式
4n平方(m-2)-6(2-m)和4m平方n平方-(m平方+n平方)平方 分解因式
1.4n^2(m-2)+6(2-m)=2(m-2)(2n^2-3)
4n平方(m-2)-6(2-m)和4m平方n平方-(m平方+n平方)平方 分解因式
(m的平方-6mn+9n的平方)÷(m-3n)-(4m的平方-9n的平方)÷(2m-3n)=
(m-2n)(4n平方-m平方)(m+2n)
m平方+2M+N平方-4N+5=0,求M,N
9m平方+【4m平方-3m-(2m平方-6m)】
已知m-n=4 m平方+n平方=10 求mn平方-m平方n 和 2m+2n 的值已知m-n=4 m平方+n平方=10 求mn平方-m平方n 和 2m+2n 的值
计算:[(m 2n)的平方-(3m n)(3m-n)-5n的平方]除以4m
已知M.N是整数,且M平方+3N平方+5〈2N(4-M)求M.N
m平方-4n的平方=6且 m-2n-2=0 则m+2n
3m-4n/2*3m+4n/3*9m的平方+16n的平方/6
已知 |2m-5|+(2m-5n+20)的平方=0 求-2m的平方-2m(5n-2m)+3n(6m-5n)-3n(4m-5n)的值
已知 |2m-5|+(2m-5n+20)的平方=0 求(-2M)的平方-2m(5n-2m)+3n(6m-5n)-3n(4m-5n)的值
2m(m-n)平方-2n(n-m)平方
m n 符合m平方-2m-1=0.n平方-2n-1=0.求2m平方+4m平方-4n+1999
(m的平方-6m+9n平方)除以(m-3n)-(4m平方-9n平方)除以(2m-3n),其中m=-3,n=-1/3
(m的平方-6m+9n平方)除以(m-3n)-(4m平方-9n平方)除以(2m-3n),其中m=-3,n=-1/3
2M平方+3N平方-MN-3M平方-4N平方+MN+6,其中M平方+N平方=5
化简求值:(5m平方-4n平方)-2(m平方-n平方)-(4m平方+n平方),其中,m=-2,n=1.